2020
DOI: 10.1016/j.tcs.2020.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Hard and easy instances of L-tromino tilings

Abstract: In this work we study tilings of regions in the square lattice with L-shaped trominoes. Deciding the existence of a tiling with L-trominoes for an arbitrary region in general is NP-complete, nonetheless, we identify restrictions to the problem where it either remains NP-complete or has a polynomial time algorithm. First, we characterize the possibility of when an Aztec rectangle has an L-tromino tiling, and hence also an Aztec diamond; if an Aztec rectangle has an unknown number of defects or holes, however, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…First, note that usual Aztec diamonds are non-tileable by n-ribbons if n 3. (For the case n = 3, see Theorem 17 in [AGMSV20].) For this reason, we consider generalized Aztec diamonds which are tileable by n-ribbons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, note that usual Aztec diamonds are non-tileable by n-ribbons if n 3. (For the case n = 3, see Theorem 17 in [AGMSV20].) For this reason, we consider generalized Aztec diamonds which are tileable by n-ribbons.…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm is linear in the area of the region. In [AGMSV20], it was shown that for general regions (which are allowed to be non-simply connected with arbitrary number of holes), the existence of tilings by 180-trominoes is an N P -complete decision problem.…”
Section: How Many Different Tilings Exist?mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a natural correspondence between domino tilings and perfect matchings in dual graphs. Likewise, Akagi et al [1] showed that tromino tilings correspond to independent sets in a slight variation of dual graphs called an intersection graph.…”
Section: Contributionsmentioning
confidence: 99%
“…Horiyama et al [6] strengthened the NP-completeness result of Moore and Robson and proved that counting the number of tromino packings of a region is #P-complete. More recently, Akagi et al [1] showed that the NP-completeness of deciding a tromino tiling heavily depends on geometrical properties of the region; for example, a region with the shape of an Aztec rectangle admits a polynomial time algorithm that decides a tromino tiling, whereas the problem remains NP-complete for an Aztec rectangle with at least two holes.…”
Section: Introductionmentioning
confidence: 99%